2018
DOI: 10.1016/j.jid.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Shining a Light on Black Holes in Keratinocytes

Abstract: The mechanisms by which melanins are transferred from melanocytes and stored within keratinocytes to generate skin pigmentation are hotly debated. In this issue, Correia and Moreiras et al. and Hurbain et al. provide evidence that melanin cores of melanosomes are secreted from melanocytes and taken up and stored within non-degradative membranous organelles in keratinocytes in the basal epidermis of human skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Melanosomes are delivered to keratinocytes via the dendrites of melanocytes (melanocyte-to-keratinocyte transfer). Melanin protects the inner microenvironment of keratinocytes, including their DNA, from UV radiation-induced damage (Wu and Hammer, 2000;Bowman and Marks, 2018). Genetic determinants regulate the quantity of melanin produced by melanocytes and the size of the melanosomes that are transferred to keratinocytes (Bessou-Touya et al, 1998).…”
Section: Melanocytesmentioning
confidence: 99%
“…Melanosomes are delivered to keratinocytes via the dendrites of melanocytes (melanocyte-to-keratinocyte transfer). Melanin protects the inner microenvironment of keratinocytes, including their DNA, from UV radiation-induced damage (Wu and Hammer, 2000;Bowman and Marks, 2018). Genetic determinants regulate the quantity of melanin produced by melanocytes and the size of the melanosomes that are transferred to keratinocytes (Bessou-Touya et al, 1998).…”
Section: Melanocytesmentioning
confidence: 99%
“…Current evidence suggests that the pathogenesis of melasma After being synthesized in melanocytes, melanin is transferred along dendrites from the perinuclear region to the dendritic terminal and transported to keratinocytes. 20 Previous studies considered that it is melanosomes transport to keratinocytes, but recent studies have confirmed that membrane-free melanocores were the main form. 21,22 In addition, the transfer is carried out by exocytosis-endocytosis.…”
Section: Discussionmentioning
confidence: 99%